Growth, mineral content and essential oil quality of buchu (Agathosma betulina) in response to ph under controlled conditions in comparison with plants from its natural habitat - Ntwana, Babalwa (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Agronomy)--University of Stellenbosch, 2007.